(untitled) - Ignizio, James P. (New York, 2009)
These are just some of the methods that, over the past five decades, have promised to transform any manufacturing firm into a lean, mean, money-making machine. While each incorporates certain fundamental truths, strengths, and benefits, they are not panaceas. Nor do they necessarily provide much-needed insight into the science that underlies factory performance.
Keywords: Production management,Quản lý sản xuất